P-222 YI Hepatitis B Immunity in Inflammatory Bowel Disease. (1st March 2016) - Watts, Abhishek; Bennett, William; Molleston, Jean; Gupta, Sandeep; Croffie, Joseph; Waseem, Shamaila; McFerron, Brian; Steiner, Steven; Vanderpool, Charles; Hon, Emily; Bozic, Molly; Subbarao, Girish; et al.
Abstract : Background: Patients with inflammatory bowel disease (IBD) often receive immunosuppressive therapy which may make them vulnerable to infections such as hepatitis B. In a healthy population, long term protection following immunization relies on immune memory. In the immunocompromised population, it is prudent to check the anti hepatitis B surface antibody (HbsAb) titer to determine protection against the hepatitis B virus (HBV). We conducted our study to determine HBV immunity in the IBD population. We hypothesize that serological HBV titers are low in the vaccinated pediatric IBD population and that this may be due to patient demographic factors or medications. The aim of our study is to identify and characterize pediatric IBD patients with low anti HbsAb titers. Methods: IBD patients ages 5 to 18 years were identified through our database, and 117 patients were prospectively enrolled. Subjects were confirmed to have had a full series of hepatitis B vaccination by obtaining records from either their primary physician or from the Children and Hoosier Immunization Registry Program (CHIRP) database. Serum HbsAb titers were measured in each of these patients. Logistic regression analysis with independent variables of age, gender, race, disease type (Crohn's versus ulcerative colitis), surgery, and medications (immunomodulators, steroids, or biologic therapy) and a dependent variable of adequate HbsAb titers (>10 mIU/mL) was performed. Results: Of the 117 patients, there were 57 males and 60 females. The mean age of the patients was 14.23 years. 16 patients were on steroids, 51 patients were on immunomodulators and 53 patients were on biologics. 29.05% of the total patients were found to be non-seroimmune. On logistic regression analysis, the p values for medications used were not statistically significant: steroids ( P = 0.94), immunomodulators ( P = 0.20), biologics ( P = 0.25). There were 75 patients with a diagnosis of Crohn's disease and 33 with a diagnosis of Ulcerative colitis with P values of 0.93 and 0.92 respectively. Nine patients in the study had been diagnosed as indeterminate colitis. Six patients had surgery performed on them ( P = 0.89). No association was found between any variables and the presence of low HbsAb titers. Conclusions: Nearly one third of pediatric IBD patients have low immunity to HBV. No patient-specific variable, such as the use of immunosuppressants, appeared to influence these low titers. This raises the possibility that waning immunity is a feature of the autoimmune process itself. Further age-matched prospective studies comparing healthy controls and children with IBD will be needed to delineate if IBD alone can lead to the waning of titers independent of other factors.